1975
DOI: 10.1126/science.170681
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transitions in Human Plasma Low Density Lipoproteins

Abstract: Thermal analysis of human plasma low density lipoproteins reveals a broad reversible transition encompassing body temperature. The calorimetric and x-ray scattering data identify this transition as a cooperation, liquid-crystalline to liquid phase change involving the cholesterol esters in the lipoprotein. This behavior requires the presence of a region rich in cholesterol ester within the lipoprotein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
0
2

Year Published

1977
1977
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(135 citation statements)
references
References 15 publications
8
125
0
2
Order By: Relevance
“…4A left face) that are potential sites where enzymes and lipid transfer proteins could interact with the phospholipid surface via their putative interfacial recognition sites. The most notable of these is cholesteryl ester transfer protein, which transports CE from HDL to LDL and very lowdensity lipoprotein (VLDL), and is known to bind to phospholipid surfaces that contain no protein (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4A left face) that are potential sites where enzymes and lipid transfer proteins could interact with the phospholipid surface via their putative interfacial recognition sites. The most notable of these is cholesteryl ester transfer protein, which transports CE from HDL to LDL and very lowdensity lipoprotein (VLDL), and is known to bind to phospholipid surfaces that contain no protein (23).…”
Section: Resultsmentioning
confidence: 99%
“…the α-helix rich and β-sheet rich domains by considering: (i) the unusual structural motifs of apo B-100 with several unusually long α helices in the two α-helix rich domains, (ii) the consensus that the apo B-100 is distributed throughout the surface of the particle (5,7,9), and lastly (iii) the scattering density difference between protein and lipids, (Fig. 4 B, C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the lipid component of LDL is emphasized in the neutron data, a temperature series between 10'C and 50 C over the complete Q range to 3.3 nm-' was studied in order to identify the phase transition in the LDL core from a liquid crystalline state at low temperature to a more disordered state [44]. A maximum was seen at Q = 1.6 n n -' at 10'C and at 20"C, which was replaced at 37°C and 50°C by another one seen at Q = 0.9 nm-'.…”
Section: Nutive Ldlmentioning
confidence: 99%
“…Although little is known about the effects of triacylglycerols in membranes, studies have already shown that the triacylglycerols have the effect of disordering the molecular organization of membrane cholesteryl ester and probably altering the lipid composition of the plasma membrane (Deckelbaum et al, 1977;Tall et al, 1978).…”
Section: Discussionmentioning
confidence: 99%